Consideration of Financial Satisfaction: What Consumers Know, Feel and Do from a Financial Perspective - Woodyard, Ann Sanders; Robb, Cliff A. (2018)
Financial satisfaction has long been considered an important component to consumer life satisfaction and well-being. Using data from the 2012 National Financial Capability Study (NFCS), financial satisfaction is explored in the context of personal characteristics related to financial knowledge (both objective and subjective) as well as self-reported financial behaviors. Ordinary Least Squares Regression is applied to a predictive model of financial satisfaction, and results indicate that measures associated with what people do (behaviors related to recommended practice) and how they feel (subjective knowledge) may be more salient factors to consider with regard to satisfaction than measures related to what individuals know (objective knowledge). Implications are considered for consumers in light of a general policy approach promoting financial literacy and education as a means of improving financial outcomes and well-being.